A Study On The Positive Impact Of Digital Visibility On Marketing For Micro, Small, And Medium Enterprises - Aviva, Itsla Yunisva; Ardiansyah, Mawar; Puspita, Widya Husna; Salim, Mohammed Salim (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2023)
This study examined the positive impact of the visibility of MSMEs in the digital world on marketing. This study used a qualitative method with a descriptive approach. The data used is secondary data. Data analysis was performed using qualitative analysis techniques. The study results show that the visibility of MSMEs has a crucial role in the sustainability of MSMEs. There are several positive impacts from the emergence of MSMEs in the digital world on marketing, such as: increasing Brand Awareness, making it easier for customers to find information, increasing the number of customers which indirectly can also increase sales and customer loyalty. In addition, there are several strategies that can be used to increase the visibility of MSMEs in the digital world related to marketing, namely building websites, using social media, doing SEO (Search Engine Optimization), creating online advertisements, and getting positive reviews. . By utilizing good digital marketing, MSMEs can more easily promote their products and services to a wider audience. In addition, it can attract more potential customers. This also allows MSMEs to more easily compete with larger companies as they can reach the same audience at a lower cost.